Vascular Streak Dieback of Cocoa in West Malaysia - Mior Ahmad, Zainal Abidin (1982)
A detailed study into vascular streak dieback (VSD), the most serious pathological problem of cocoa in Malaysia was carried out. The causal pathogen was isolated and the symptomatology relating to infection of mature cocoa and seedling in the nurseries has been described. Morphological studies of the local isolates have confirmed the close similarity of the VSD fungus to Oncobasidium theobromae Talbot and Keane, described as the primary causal agent of VSD in Papua New Guinea. Techniques useful for isolation of the pathogen in routine and sequential samplings were investigated. The use of nutrient poor medium, surface treatment of infected materials and plating samples within 48 hours after collection from the field had improved the efficiency of isolation of the VSD pathogen. The leaf isolation technique developed is a rapid and non-destructive method for isolation of the pathogen and confirmation of VSD incidence especially in seedlings in the nursery. A survey of the disease undertaken confirmed incidence of VSD in mature plantings in the states of Trengganu, Johor, Perak and Malacca; cocoa nurseries in Perak and Johor; and clonal plantings in Negeri Sembilan. In all cases, the percentage incidence and severity varied from locality to locality. Generally, the survey of clonal plantings had provided information On the relative susceptibility within clones. The fungus hitherto recorded to grow poorly On artificial media, had been found to grow satisfactorily on Corticium culture medium and On Leonian's solution agar.